The Imaginary : A Phenomenological Psychology of the Imagination - Sartre, Jean-Paul 1905-1980; Webber, Jonathan (London Routledge, 2004)
First published in 1940, Sartre's "The Imaginary" is a cornerstone of his philosophy. Sartre had become acquainted with the philosophy of Edmund Husserl in Berlin and was fascinated by his idea of the "intentionality of consciousness" as a key to the puzzle of existence. Against this background, "The Imaginary" crystallized Sartre's worldview and artistic vision. Here he presented the first
Originally published in 1940
Keywords: Husserl, Edmund -- 1859-1938; 20th Century (1901-2000); Philosophy; Imagination; France